Special-Lofa County Agriculture Development Project (African Knowledges and the History Publication since the 1970s)
A talk show about the history and impact of the Lofa County agriculture development project, its impact on the lives of the inhabitants of Lofa County and its funding sources.
Keywords: Education; Agriculture